MEDICALIZATION OF LEARNING AND RESILIENCE: SIGNIFICATIONS DEVELOPED IN SCHOOLS - Santos, Regina Lemes dos; Oliveira, Francismara Neves de; Battistella Bianchini, Luciane Guimaraes [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This paper broaches the promotion of resilience by analyzing signification developed within the context of students diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) using the medicine methylphenidate hydrochloride (Ritalin or Concerta) The Bio-ecological model of Human Development was adopted as a theoretical-methodological contribution. The research followed the qualitative approach of descriptive-interpretative nature comprising 40 people, namely: health staff (1 neuropediatrician, 1 psychologist); education staff (5 pedagogues, 11 teachers); 10 students and 12 family members. The data were collected by means of interview within a context including six county schools in a Northern Parana State town. The results pointed out the need to rethink the current assessment practices and showed that the diagnostic process is defined both by risk factors and protection, which affect the school learning process. The data allowed us of conclude that the promotion of resilience, under that circumstance, may result in the establishment of affective support networks provided to family members and students using that medicine. Such a context would result in conditions more favorable to link the student to the school and positive changes in the school learning process of students diagnosed with ADHD.
Keywords: Resilience; Bio-ecological theory of human development; TDAH; Medicalization of learning; Ritalin